Variation in Structure and Location of VanA Glycopeptide Resistance Elements among Enterococci from a Single Patient - Tremlett, Catherine H. (American Society for Microbiology, 1999)
Forty-six VanA glycopeptide-resistant enterococci (GRE) from a single patient were investigated for variation in structure and location of VanA resistance elements. Together with identification to species level and pulsed-field gel electrophoresis, these data divided the GRE into 10 groups and subgroups. Combining data in this manner appears helpful when investigating the epidemiology of GRE.